The outcome of pregnancies after bariatric surgery: an observational study of pregnancies during 2004-2016 in Finland - Kaukonen Sesilia; Pajula Susanna; Koljonen Virve; Gissler Mika; Ulander Veli-Matti; Kaijomaa Marja (Springer Heidelberg, 2025)
Purpose: Overweight and obesity are major risk factors for perinatal morbidity and mortality, and the need for bariatric surgery (BS) among fertile-aged women is increasing. This study evaluates the outcome of post-BS pregnancies and deliveries.
Methods: All 20-45-year-old patients delivering between 2004 and 2016 in Finland were included. Patients with previous BS were identified from the hospital discharge register, and the medical birth register was queried for data on pregnancies, deliveries, and perinatal outcomes. The data were matched using personal identification codes, and the outcomes of women with previous BS were compared with those of other pregnancies.
Results: Women with previous BS (n = 314) constituted the bariatric group. When compared with the non-bariatric group (n = 750,019), they were older (p < 0.001), heavier (p < 0.001) and had more previous pregnancies (p < 0.001). The overall incidence of pregnancy-induced hypertension (p = 0.002), gestational diabetes (GDM) (p = 0.018), pre-term contractions (p = 0.023), pre-term delivery (p = 0.003), labour induction (p < 0.001), planned (p = 0.001) and unplanned (p = 0.036) caesarean sections and low birthweight infants (p < 0.001) were significantly higher in the bariatric group. When compared with body mass index-specific categories, the main outcomes were increased incidence of GDM and small for gestational age (SGA) newborns in the bariatric group.
Conclusion: BS can be considered a safe and advisable treatment for obesity among fertile-aged women. The pregnancy outcome is associated with post-BS weight, but the risk for GDM and small for gestational-age newborns is increased.